"We will change whether we want it or not": Soil erosion in Maasai land as a social dilemma and a challenge to community resilience. (December 2019) - Rabinovich, Anna; Kelly, Claire; Wilson, Geoff; Nasseri, Mona; Ngondya, Issakwisa; Patrick, Aloyce; Blake, William H.; Mtei, Kelvin; Munishi, Linus; Ndakidemi, Patrick
Abstract: Soil erosion is a major environmental challenge that undermines economic development in many regions of the world. While much previous work explored physical processes behind this problem, less attention has been paid to social, cultural, and psychological parameters that make a significant impact on soil erosion through the land use practices that they support. The present paper addresses this gap by conducting a qualitative exploration of agro-pastoralist stakeholders' experiences of soil erosion in northern Tanzania, using the community resilience framework and the social dilemmas approach as theoretical lenses. Interview data suggests that the factors that make communities vulnerable to soil erosion challenges include the centrality of cattle keeping practice to pastoralists' cultural identity, lack of social cohesion, lack of alternative livelihood opportunities, and weak governance structures. We argue that the ways towards resolving the dilemma lie in addressing relevant cultural norms, building cohesive and open communities, and strengthening local governance. Highlights: Soil erosion on Maasai land represents a typical example of the commons dilemma. Difficulty in tackling it is linked to lack of cohesion and cattle ownership norms. Community resilience in this context is weak to moderate across domains. Solutions lie in addressing relevant norms and building cohesive communities.